ØªØ·ÙˆÙŠØ± ÙˆØ§Ø³Ø·Ø© Ø§Ù„ØªÙØ§Ø¹Ù„ÙŠØ© Ø¨Ø¹Ø±Ø¶ ØªÙ‚Ø¯ÙŠÙ…Ù‰ Ø¹Ù„Ù‰ Ù…ÙˆØ§Ø¯ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Faizatun solihah; Moh Riadhi; Suaidi Suaidi (Lughatu Ad-Dhat, 2022)
The background of this research is that the use of an interactive medium with a presentation is not maximized when learning the Arabic language. Therefore, it is necessary to develop an interesting interactive medium to facilitate the students' understanding of the Arabic language materials presented in class. This research aims to describe the stages of developing an educational medium in the form of an interactive medium with a presentation, describe the quality of an educational medium developed in the form of an interactive medium with a presentation, and describe the results of students' learning from developing an interactive medium with a presentation. This research is research development (R&D). The development model used is the ADDIE development model. The ADDIE development model has phases, namely analysis, design, development, implementation, and evaluation.The results of this research consist of two aspects, namely, media quality and student learning outcomesThe material experts rating gets a score of 91%. Media experts' ratings have a score of 88%. Evaluation by students gets a score of 88%. Students' learning outcomes obtained pre-test scores with an average educational score of 64.6774. While the test scores got an average of 80.4834 learning results. The results of this research were tested through